The Value of Fine-Needle Aspiration Biopsy (FNAB) in Differential Diagnosis of Scintigraphic Cold Thyroid Nodule - Sulejmanovic, Maja (Acta Inform Med, 2019)
INTRODUCTION: Pathology of thyroid nodules is present in all ages and it is frequently encountered in clinical practice. Thyroid nodules do not represent a single disease, but they are the clinical manifestation of a wide range of different thyroid diseases. AIM: The objective of this study is to evaluate the frequency and localization of malignancy in solitary scintigraphic cold nodules, as well as the sensitivity, specificity and diagnostic accuracy of FNAB in comparison with histopathological findings. METHODS: The study was included 49 patients with palpatory findings of the solitary nodule located in the both lobes or isthmus of thyroid gland. All subjects underwent the scintigraphy and FNAB, followed by a cytologic results that was compared to the final histopathological diagnosis, after surgery. RESULTS: The study results show that the highest number of solitary nodules (81,6%) is localized in the lower pole of the both lobes of the thyroid gland. The cytologic results were benign 8 cases, malignant in 23 and indeterminate (follicular neoplasm) in 18 cases. The highest number of thyroid cancer is histopathologically confirmed in the patients with cytological diagnosis of follicular neoplasms, i.e. follicular cancer is found in 66.7% and papillary cancer is found in 33.3% of subjects. The most common cancer is papillary cancer found in 61,2%. Since the pathohistological diagnosis of all our patients responded to cancer, it was done indirect statistical evaluation of the diagnostic sensitivity of cytological method in the estimation of malignant thyroid lesion, which was 83,7%. CONCLUSION: FNAB is a highly sensitive method in the diagnostics of malignant thyroid lesions with the sensitivity Se=83,7%. The highest number of thyroid cancer is histopathologically confirmed in the patients with cytological diagnosis of follicular neoplasm (66.7%). The highest number of patients had a cytological diagnosis of papillary cancer.